Dolutegravir versus efavirenz in women starting HIV therapy in late pregnancy (DolPHIN-2): an open-label, randomised controlled trial. Issue 5 (May 2020) - Kintu, Kenneth; Malaba, Thokozile R; Nakibuka, Jesca; Papamichael, Christiana; Colbers, Angela; Byrne, Kelly; Seden, Kay; Hodel, Eva Maria; Chen, Tao; Twimukye, Adelline; Byamugisha, Josaphat; Reynolds, Helen; et al.
Summary: Background: Late initiation of HIV antiretroviral therapy (ART) in pregnancy is associated with not achieving viral suppression before giving birth and increased mother-to-child transmission of HIV. We aimed to investigate virological suppression before giving birth with dolutegravir compared with efavirenz, when initiated during the third trimester. Methods: In this randomised, open-label trial, DolPHIN-2, we recruited pregnant women in South Africa and Uganda aged at least 18 years, with untreated but confirmed HIV infection and an estimated gestation of at least 28 weeks, initiating ART in third trimester. Participants were randomly assigned (1:1) to dolutegravir-based or efavirenz-based therapy. HIV viral load was measured 7 days and 28 days after antiretroviral initiation, at 36 weeks' gestation, and at the post-partum visit (0–14 days post partum). The primary efficacy outcome was a viral load of less than 50 copies per mL at the first post-partum visit, and the primary safety outcome was the occurrence of drug-related adverse events in mothers and infants until the post-partum visit. Longer-term follow-up of mothers and infants continues. This study is registered with ClinicalTrials.gov, NCT03249181 . Findings: Between Jan 23, and Aug 15, 2018, we randomly assigned 268 mothers to dolutegravir (135) or efavirenz (133). All mothers and their infants were included in the safety analysis, and 250 mothers (125 in the dolutegravir group, 125 in the efavirenz group) and their infants in efficacy analyses, by intention-to-treat analyses. The median duration of maternal therapy at birth was 55 days (IQR 33–77). 89 (74%) of 120 in the dolutegravir group had viral loads less than 50 copies per mL, compared with 50 (43%) of 117 in the efavirenz group (risk ratio 1·64, 95% CI 1·31–2·06). 30 (22%) of 137 mothers in the dolutegravir group reported serious adverse events compared with 14 (11%) of 131 in the efavirenz group (p=0·013), particularly surrounding pregnancy and puerperium. We found no differences in births less than 37 weeks and less than 34 weeks gestation (16·4% vs 3·3%, across both groups). Three stillbirths in the dolutegravir group and one in the efavirenz group were considered unrelated to treatment. Three infant HIV infections were detected, all in the dolutegravir group, and were considered likely to be in-utero transmissions. Interpretation: Our data support the revision to WHO guidelines recommending the transition to dolutegravir in first-line ART for all adults, regardless of pregnancy or child-bearing potential. Funding: Unitaid.